2019
DOI: 10.18433/jpps30622
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and Stimulatory Effects of Selective Serotonin Reuptake Inhibitors on Cytochrome P450 2D6-mediated Dopamine Formation from p-Tyramine

Abstract: PURPOSE: The effects of selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine and paroxetine on dopamine formation from p-tyramine, mediated by cytochrome P450 (CYP) 2D6.2 (Arg296Cys, Ser486Thr) and CYP2D6.10 (Pro34Ser, Ser486Thr), were compared with their effects on CYP2D6.1 (wild type)-mediated dopamine formation, to investigate the influence of a CYP2D6 polymorphism on neuroactive amine metabolism in the brain. METHODS: The Michaelis constants (Km) and maximal velocity (Vmax) values of dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In stressed rats treated with escitalopram or venlafaxine, it was found that activity of CYP2D was increased in brain but decreased in liver . Other antidepressants such as paroxetine inhibited brain CYP2D activity (Niwa and Sugimoto, 2019). In vivo data showed that effects of psychotropic drugs on rat brain CYP2D were dependent on brain regions.…”
Section: Depressive Disorder and Psychotropic Medicationsmentioning
confidence: 99%
“…In stressed rats treated with escitalopram or venlafaxine, it was found that activity of CYP2D was increased in brain but decreased in liver . Other antidepressants such as paroxetine inhibited brain CYP2D activity (Niwa and Sugimoto, 2019). In vivo data showed that effects of psychotropic drugs on rat brain CYP2D were dependent on brain regions.…”
Section: Depressive Disorder and Psychotropic Medicationsmentioning
confidence: 99%